Diseño de material didáctico estructurado con sistema braille, como apoyo educativo para mejorar el proceso de enseñanza aprendizaje de personas ciegas totales y de baja visión en la asociación provincial de discapacitados visuales de Chimborazo APRODVICH. - Guamán Chiro, Germán Enrique (2020)
Graphic design proposes solutions to visual needs that can be interpreted not only by sight, but also by haptic science through touch. It is in this nature that the graphic designer plays a fundamental role and is aware of the problems that arise within the context, and it is committed to solve the problems of people who are visually impaired. For this reason, the present project called "Design of Braille system structured, didactic material as an educational support to improve the teaching and learning process of people with total blind and low vision in the provincial association of visually impaired people of Chimborazo APRODVICH", it has the purpose of applying the of the career knowledge to design a structured didactic material, which supports the teaching-learning process in the basic area of reading and writing Braille in the Association. For the development of this project, instruments were applied to the teachers of the area and experts in graphic design with the purpose of identifying problems with the didactic materials used in the class of this area, that will be helpful, to give a quick solution to the investigated problem, achieving that the obtained product has as purpose to help and strengthen the teaching-learning process in the basic area of reading-writing Braille. For which five proposals of didactic materials were developed; Domino cards for the figures and letters association. Puzzles to assemble words, syllables and sentences. Crossword puzzle board to identify and associate pictograms with words. Didactic educational counter to strengthen the knowledge acquired about vowels and finally tales for figures and writing recognition.